Kompetensi Mengajar Guru PPKn Ditinjau Dari Mood Swingnya Dalam Mengajar Di Sekolah SMA Budisatrya Medan - Fahrysyah Aulya; Adelina Sitanggang; Bertania Permata Sari; Mira Cahya; Nur Hidayah Hasibuan; Muhammad Iraqi Fauzi; Jamaludin Jamaludin (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This research aims to determine the teaching competence of Civic Education teachers in terms of their Mood Swing in teaching at Budisatrya Medan High School. The method used is a qualitative method with a descriptive-analytic approach, by collecting data through interviews with students and teachers, as well as observations in the school environment. The results of the research show that teachers at Budi Satrya High School Medan have quite fluctuating moods. Factors that influence teachers’ mood swings , both internal factors (health conditions, personal problems, and stress levels) and external factors (class conditions, support from the school, and work pressure), have a significant impact on decreasing motivation, creativity, and teacher performance in teaching during the learning process. Changes in a teacher’s mood are influenced by various factors, such as health conditions, personal problems, and dynamics in the classroom. It is hoped that this research can contribute to the development of knowledge of civic education teachers’ teaching competencies in terms of their mood swings in teaching at school